IL‐17 is associated with disease severity and targetable inflammatory processes in heart failure - Lukas Baumhove; Bart J. vanEssen; Martin M. Dokter; Sietske N. Zijlstra; Frederik E. Deiman; Jon D. Laman; Chim C. Lang; Gwenny M.P.J. Verstappen; Dirk J. vanVeldhuisen; Peter van derMeer; Nils Bomer; Adriaan A. Voors (ESC Heart Failure, 2024)
Abstract Aims Heart failure (HF) is recognized as an inflammatory disease in which cytokines play an important role. In animal HF models, interleukin‐17A (IL‐17) has been linked to deterioration of cardiac function and fibrosis, whereas knock‐out of IL‐17 showed beneficial cardiac effects. However, there is limited evidence of IL‐17 involvement in patients with HF. This study aims to investigate the clinical characteristics, outcomes, and pathophysiological processes associated with circulating IL‐17 concentrations in patients with HF. Methods and results IL‐17 was measured by ELISA in 2082 patients diagnosed with HF along with 363 circulating proteins using proximity extension assay technology for differential expression and pathway analysis. Data were validated in an independent cohort of 1737 patients with HF. Patients with elevated IL‐17 concentrations had more severe HF, as reflected by more frequent current or previous hospitalizations for HF, higher New York Heart Association functional class (NYHA) and higher levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP). High IL‐17 concentrations were independently associated with an increased risk of hospitalization for HF and mortality. In both cohorts, the most strongly up‐regulated proteins in patients with high IL‐17 were fibroblast growth factor 21 (FGF‐21), interleukin‐6 (IL‐6), C‐X‐C motif chemokine ligand 13 (CXCL13), tumour necrosis factor receptor superfamily member 6B (TNFRSF6B) and interleukin‐1 receptor antagonist (IL‐1RA). Pathway over‐representation analysis showed increased activity of pathways related to lymphocyte‐mediated immunity, leukocyte activation and regulation of the immune response. Conclusions In patients with HF, elevated IL‐17 concentrations indicate more severe HF and increased activity of inflammatory processes known to be involved in the pathophysiology of HF. IL‐17 might hold potential for identifying and targeting inflammation in HF.